Microcredit position in micro and small enterprise performance: The Malaysian case - Mahmood, R.; Rosli, M.M. (2013)
Purpose: This paper aims to evaluate the microcredit position in the performance of micro and small enterprises (MSEs). In the case of Malaysian MSEs, the paper also aims to examine other relevant factors, especially entrepreneur‐specific factors, which may be equally important for improving firm performance. Design/methodology/approach: Primary data were collected from 756 MSE samples in Kelantan, the state where a large majority of the microcredit recipients under AIM and TEKUN run their business. Descriptive and multiple regression analyses were used to analyze the data. Findings: Microcredit is positively and significantly related to the performance of MSEs across all the microcredit programs under investigation. Other entrepreneur‐specific factors, especially entrepreneurial values and management practices are equally significant for enhancing firm performance. Practical implications: This study reminds policy makers, support institutions and small entrepreneurs that the microcredit program alone is not enough for improving the performance of MSEs. Besides microcredit, entrepreneur‐specific factors are equally important for firm performance. Thus, readjustment to the existing microcredit programs, especially on entrepreneurial and managerial developments, should be made so that entrepreneurial values and management competencies of the entrepreneurs could be enhanced from time to time for superior performance of MSEs. Originality/value – This paper proves that microcredit is important for firm performance. It also reminds theorists and practitioners that entrepreneur‐specific factors should not be neglected in their theoretical or practical consideration of micro and small firm performance.